Development of a Modified Friedewald’s Formula to Calculate Low-Density Lipoprotein in an Iranian Population - Sobhani, Seyed Alireza; Kheirandish, Masoumeh; Rafati, Shideh; Rafat, Milad; Shahbazi, Roghayeh; Azarbad, Abnoos; Mahmoodi, Masoumeh (Shiraz University of Medical Sciences, 2023)
Background: Elevated low-density lipoprotein cholesterol (LDL-C) is a significant risk factor for cardiovascular diseases. LDL-C can be directly measured using various methods, but this requires expensive equipment. Currently, clinical laboratories estimate LDL-C based on Friedewald’s formula (FF). We aimed to develop a modified formula based on directly measured LDL-C (D-LDL-C) values in a large population in Southern Iran and compare the results with various other estimation formulas. Methods: The participants of this cross-sectional study were adults aged >18 years living in Southern Iran. Blood samples from 15,200 individuals were collected, and the measured lipid parameters were randomly divided into training (n=10,184) and validation (n=5,016) datasets. A new formula was developed using a linear regression model, and its accuracy was validated. Pearson’s correlation and Cohen’s kappa were used to determin the relationship between D-LDL-C and calculated LDL-C (C-LDL-C). Results: The developed formula for the estimation of LDL-C was 0.857 total cholesterol (TC)-0.915 high-density lipoprotein cholesterol (HDL-C)-0.115 triglycerides (TG). Based on our proposed formula, for TG<150 and TG?150 mg/dL, there was a significant correlation between mean values of D-LDL-C and C-LDL-C (r=0.985 and r=0.974, respectively). Compared to other formulas, C-LDL-C obtained from the proposed formula had the highest correlation with D-LDL-C. The agreement between D-LDL-C and C-LDL-C for TC<200, 200-239, and ?240 mg/dL was 80.8%, 63.2%, and 67.4%, respectively, indicating a higher level of agreement than other formulas. Conclusion: The new formula appears to be more accurate than FF when applied to the population of Southern Iran. © 2023, Shiraz University of Medical Sciences. All rights reserved.
Keywords: Cardiovascular diseases; Cholesterol; HDL; Iran; LDL; Lipoproteins